Pengaruh Brand Ambassador Baekhyun Exo Melalui Instagram Terhadap Brand Image Allobank - Grasheila Febrina Widiatmoko Putri; Delmarrich Bilga Ayu Permatasari; Muhammad Fadeli (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2024)
The development of digital industry in Indonesia continues to experience a significant increase, especially in the banking world. The presence of various new digital banks will cause intense competition in capturing market potential. In this condition, it makes one of the digital bank companies AlloBank compete to build a strong brand image by using brand ambassadors to attract the attention of its customers through AlloBank's official Instagram account. The presence of South Korean culture in various circles of Indonesian society made the AlloBank company choose Baekhyun EXO, who is a Korean idol, as its brand ambassador. The existence of this phenomenon, this study aims to see whether there is an influence of Baekhyun EXO's brand ambassador which is studied using VisCAP theory on AlloBank's brand image. This research uses quantitative methods by distributing questioners to 100 respondents who are followers of AlloBank's official Instagram account. The data analysis technique in this study uses the Simple Linear Regression test which is carried out using Jamovi. The research results show that brand ambassador Baekhyun EXO has a significance value of <0.001 (<0.05) and a positive influence on AlloBank's brand image of 22%, while 78% is influenced by factors other than the brand ambassador